Gene expression analysis of the concomitant existence of lymphovascular and perineural invasion in colorectal cancer - Nadiah Abu,; Nurul-Syakima Ab Mutalib,; Rahman Jamal, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
The invasion of cancer cells into the peritumoral, lymph node and perineural system could be detrimental on cancer patients. In colorectal cancer (CRC) patients, the presence of lymphovascular (LVI) and/or perineural (PNI) invasion could significantly influence on the survival rates, treatment options and recurrence tendencies. To date, no study has analyzed the molecular profile of the concomitant existence of LVI and PNI in CRC. Here, we reanalyzed The Cancer Genome Atlas (TCGA) CRC datasets and focused on cases where the information regarding LVI and PNI are available (n=176). We performed differential gene expression, methylation and microRNA analysis by comparing the groups having both or either LVI and PNI with the control group (LVI negative and PNI negative). Although there was no significant difference in the methylation and miRNA profiles, we identified a number of differentially expressed genes (DEGs). The comparison between the LVI+PNI+ and LVI-PNI- groups revealed key DEGs including SFTA2, PHACTR3, CRABP2, ODZ3, GRP, HAP1, CSDC2, TMEM59L and HDAC9. Meanwhile, in the LVI-PNI+ vs LVI-PNI- group, some of the DEGs found were PTPRR, EFNA2, FGF20, IGFL4, METRN and IGFBPL1. We believe that this study could be beneficial and add value to further understand the complex molecular profiles of CRC.